2008
DOI: 10.1213/ane.0b013e31817ef110
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Silicone Wire-Reinforced Tube with the Parker and Polyvinyl Chloride Tubes for Tracheal Intubation Through an Intubating Laryngeal Mask Airway in Patients with Normal Airways Undergoing General Anesthesia

Abstract: Manipulation improved the success rate of intubation with the Parker tube through the ILMA rendering it a possible alternative to the silicone wire-reinforced tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…who compared the ease of intubation using WRS tube, Parker tube, and PVC tube through the ILMA. [5] They reported a success rate of 90%, 54%, and 48%, respectively, for the 3 groups without the use of manipulations and 90%, 86%, and 57%, respectively, with manipulations. The difference could be attributed to limited clinical experience in using PVC tubes with ILMA and the small sample size in their study.…”
Section: Discussionmentioning
confidence: 99%
“…who compared the ease of intubation using WRS tube, Parker tube, and PVC tube through the ILMA. [5] They reported a success rate of 90%, 54%, and 48%, respectively, for the 3 groups without the use of manipulations and 90%, 86%, and 57%, respectively, with manipulations. The difference could be attributed to limited clinical experience in using PVC tubes with ILMA and the small sample size in their study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Due to its blunt tip, this tube is well-suited for blind insertion through the FT-LMA. It is important to maintain the orientation of the external black longitudinal line of the ETT with the patient's nose to insure the bevelled tip is appropriately oriented at the glottic opening.…”
Section: Endotracheal Tube Selectionmentioning
confidence: 99%
“…The use of a standard polyvinylchloride (PVC) ETT is feasible, but the success rates are lower with blind insertion because of the left-sided bevel and the propensity for arytenoid cartilages or false or true vocal cords to obstruct insertion. Kanazi et al 15 demonstrated a low first attempt success rate of 48% using a standard ETT that increased to only maximal. This ''first'' maneuver aligns the internal aperture with the glottic opening.…”
Section: Endotracheal Tube Selectionmentioning
confidence: 99%
“…Kanazi et al . [15] reported 90% overall success rate with FTST compared with 57% with PVCT. This lower success rate was attributed to the impingement of the tip of the ETT on the tubercle of the epiglottis.…”
Section: Discussionmentioning
confidence: 99%